Foaming of 3d-Printed Pla/Caco3 Composites by Supercritical co2 Process for Sustainable Food Contact Materials - Romero-Figueroa, J; Galotto-Lopez, M; Torres-Mediano, A; Riveros-Faba, S (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
In the last decade, among the emerging technologies in the area of bioplastics, additive manufacturing (AM), commonly referred to as 3D printing, stands out. This technology has gained great interest in the development of new products, mainly due to its capability to easily produce customized and low-cost plastic products. This work aims to evaluate the effect of supercritical foaming of 3D-printed parts based on a commercial PLA matrix loaded with calcium carbonate, for single-use sustainable food contact materials. 3D-printed PLA/CaCO3 parts were obtained by 3D printing with a 20% and 80% infill, and two infill patterns, rectilinear and triangular, were set for each of the infill percentages selected. Supercritical fluid foaming of PLA/CaCO3 composite printed parts was performed using a pressure of 25 MPa, a temperature of 130 °C for 23 min, with a fast depressurization rate (1 s). Closed-cell foams were achieved and the presence of CaCO3 did not influence the surface of the foams or the cell walls, and no agglomerations were observed. Foam samples with 80% infill showed subtle temperature fluctuations, and thermogravimetric analysis showed that samples were thermally stable up to ~300 °C, while the maximum degradation temperature was around 365 °C. Finally, tensile test analysis showed that for lower infill contents, the foams showed lower mechanical performance, while the 80% infill and triangular pattern produced foams with good mechanical performance. These results emphasize the interest in using the supercritical CO2 process to easily produce foams from 3D-printed parts. These materials represent a sustainable alternative for replacing non-biodegradable materials such as Expanded Polystyrene, and they are a promising option for use in many industrial applications, such as contact materials. © 2024 by the authors.